'

Równania wyższych stopni cz. 2 [CAŁOŚCIOWE OMÓWIENIE]

Przykład 1

Rozwiąż równanie:
a) $latex \left( {{{\text{x}}^{2}}+3\text{x}} \right)\left( {\text{x}-5} \right)=0$
b) $latex \left( {{{\text{x}}^{2}}-7\text{x}} \right)\left( {\text{x}+1} \right)=0$
c) $latex \left( {5{{\text{x}}^{2}}+\text{x}} \right)\left( {\text{x}-4} \right)=0$
d) $latex \left( {8\text{x}-1} \right)\left( {{{\text{x}}^{2}}+2\text{x}} \right)=0$
e) $latex \left( {\text{x}+5} \right)\left( {\text{x}-3} \right)\left( {{{\text{x}}^{2}}+1} \right)=0$
f) $latex \left( {\text{x}+1} \right)\left( {\text{x}+2} \right)\left( {{{\text{x}}^{2}}+3} \right)=0$
g) $latex 3\text{x}\left( {{{\text{x}}^{2}}+5} \right)\left( {2-\text{x}} \right)\left( {\text{x}+1} \right)=0$
h) $latex {{\text{x}}^{2}}\left( {\text{x}+5} \right)\left( {2\text{x}-3} \right)\left( {{{\text{x}}^{2}}-7} \right)=0$
i) $latex \left( {{{\text{x}}^{3}}+125} \right)\left( {{{\text{x}}^{2}}-64} \right)=0$
j) $latex \left( {{{\text{x}}^{2}}-6} \right)\left( {3\text{x}+2} \right)=0$

Przykład 2

Rozwiąż równanie:
a) $latex {{\text{x}}^{3}}-2{{\text{x}}^{2}}+\text{x}=0$
b) $latex {{\text{x}}^{3}}+{{\text{x}}^{2}}+\text{x}=0$
c) $latex {{\text{x}}^{3}}-10{{\text{x}}^{2}}+25\text{x}=0$
d) $latex {{\text{x}}^{3}}-4{{\text{x}}^{2}}+3\text{x}=0$
e) $latex {{\text{x}}^{3}}+2{{\text{x}}^{2}}-3\text{x}=0$

Przykład 3

Rozwiąż równanie:
a) $latex {{\text{x}}^{3}}-7{{\text{x}}^{2}}-4\text{x}+28=0$
b) $latex {{\text{x}}^{3}}-3{{\text{x}}^{2}}+2\text{x}-6=0$
c) $latex {{\text{x}}^{3}}+4{{\text{x}}^{2}}-9\text{x}-36=0$
d) $latex {{\text{x}}^{3}}-6{{\text{x}}^{2}}-9\text{x}+54=0$
e) $latex {{\text{x}}^{3}}+2{{\text{x}}^{2}}-8\text{x}-16=0$
f) $latex 3{{\text{x}}^{3}}-4{{\text{x}}^{2}}-3\text{x}+4=0$
g) $latex {{\text{x}}^{3}}-6{{\text{x}}^{2}}-12\text{x}+72=0$
h) $latex 9{{\text{x}}^{3}}+18{{\text{x}}^{2}}-4\text{x}-8=0$
i) $latex {{\text{x}}^{4}}-2{{\text{x}}^{3}}+27\text{x}-54=0$